Effect of Tire Lug Height, Forward Speed and Cast Iron Ballast on Tractor Performance - A. Muhieldeen, Osama; A. Rahama, Omer; I. Mohamed, Hassan (Gezira Journal of Agricultural Science; Vol 3 No 1 (2005), 2021)
The study was conducted at El Rahad Agricultural Scheme (Block 8( Sudan, during the period Feb.-May 1996 where the soil is a heavy cracking clay. The objective of the study was to improve the performance of the tractor when worn tires were used. The performance of the tractor, wheel slippage, fuel consumption and field capacity of the tractor were measured. Three levels of tire lug height were used, namely, 35 mm (new tire), 20 mm (medium worm tire) and zero mm (fully worn tire). Four levels of cast iron ballast were used, namely, zero, 63, 126 and 252 kg were distributed between rear tires. Moreover, three levels of tractor forward speed (5.6, 6.9 and 10.6 km/hr) were employed. The results indicated that there was a significant improvement in tractor performance when using worn tires through the use of cast iron ballast on the rear wheels. It was found that tires with zero mm lug height and 252 kg cast iron ballast decreased tractor wheel slippage and fuel consumption by34% and 18%, respectively, and increased tractor field capacity by 16.2 % Moreover, when tires with 20 mm lug height and 252 kg cast iron ballast were used, the slippage and fuel consumption were decreased by 41.7 % and 18.2%, respectively, and tractor field capacity was increased by 14.5%. The tractor with tires lug height of 35 mm and 252 kg cast iron ballast, decreased slippage and fuel consumption by 22% and 11.5%, respectively, and increased tractor field capacity by 13.5%.